Balinese Traditional Literature as a Medium for Ethnopedagogy: Exploring Cultural Contexts to Improve Elementary Students’ Conceptual Understanding - Antara, I Gede Wahyu Suwela (International Journal of Language and Literature, 2024)
Many elementary students struggle to comprehend abstract mathematical concepts due to a lack of connection with their real-life experiences. This study explores how Balinese traditional literature can serve as a medium for ethnomathematics to enhance students’ mathematical literacy. Using a qualitative approach, the research involved six teachers and elementary students. Data were collected through classroom observations, teacher interviews, and analysis of Balinese traditional texts. The findings indicate that integrating traditional literature into mathematics instruction enhances student engagement, deepens conceptual understanding, and develops problem-solving skills through contextual examples. These results align with previous research emphasizing the role of ethnomathematics in culturally responsive mathematics education. However, challenges such as limited resources and the need for teacher training were also identified. This study contributes to the development of more meaningful and context-based mathematical learning approaches in elementary education. Future research should focus on developing ethnomathematics-based learning resources and assessing the long-term impact of this method on students’ mathematical literacy.